Lessons Learned from the British: The Liverpool Project - Claudia J McVicker (Educational Considerations, 2019)
Universities around the country are beginning to feel the need to add a global dimension to their programs. One way to prepare teachers to address the challenges associated with teaching children in a global age is through carefully structured, international study abroad where the candidates are immersed in another culture and school system. This article seeks to demonstrate how a successful Teacher Education study abroad program can develop and transform pre-service candidates’ global perspective. This qualitative study was informed by the use of journal writing to prompts by ninety-six teacher education students over three different summers to learn about the Literacy Hour used in British schools during a study abroad conducted during an 8-week immersive learning experience in a setting in a northern British city. Readers will learn from participants themselves through carefully reported vignettes that focus on four themes that emerged in data analysis: Global Awareness, Retrospective Appreciation of U.S. schools based on British Literacy Practices, Teaching Self-Efficacy, and Travel Maturity.
Keywords: Study Abroad; global awareness; Literacy Hour; Teacher Education